The verb in archaic Biblical poetry: a discursive, typological, and historical investigation of the tense system - Notarius, Tania (Studies in Semitic languages and linguistics, 2013)
The Verb in Archaic Biblical Poetry by Tania Notarius suggests a discursive, formal, and historical-linguistic analysis of the tense system in the corpus of "archaic" biblical poetry